Analysis of the Implementation of Regional Regulation No. 3 of 2019 Concerning Smoke-Free Area Policy in Palopo City - Nur Indah Sari,; Balqis Nazaruddin,; Indar,; Amran Razak,; A. Arsunan Arsin,; Muhammad Lalu Saleh,; Anwar Mallongi, (International Journal of Medical Toxicology and Legal Medicine, 2024)
The Palopo City Government has a Smoke-Free Area (KTR) policy to reduce the negative impacts of cigarettes, but its implementation is still ineffective and violations by the community remain a problem that must be addressed.Analyzing the Implementation of Palopo City Regional Regulation Number 3 of 2019 concerning Smoke-Free Areas in Palopo City. This type of research uses qualitative analysis with a descriptive approach to explore phenomena and information, where informants consist of key informants and supporting informants.The enforcement of the KTR Regional Regulation in Palopo City has not been effective, with many violations by the community despite support from policy makers and implementers. There are no resources, budgets, and facilities such as KTR signs and stickers to support the policy. In addition, the bureaucratic structure has not been running effectively because there is no clear authority, SOP, or implementation guidelines.The enforcement of the Smoke-Free Area (KTR) Regional Regulation in Palopo City has not been effective, despite support from policy makers and implementers. The main obstacles include the lack of resources, budget, supporting facilities, and a bureaucratic structure that has not been running optimally due to the absence of clear authority and SOP.